Emotional intelligence trends in nursing education: review the literature - Matroud, Fouziyah; Othman, Mohd Syaubari; Mohd Jamil, Mohd Ridhuan; Hosshan, Hasrul; Md Zabit, Mohd Nazir; Yahya, Faridah Hanim; Azhari Azman, Mohamed Nor; Setambah, Mohd Afifi Bahurudin (International Journal of Public Health Science (IJPHS), 2025)
The high demand for nursing work to encounter death or disease, dealing with a high volume of work in a short amount of time, working under intense pressure, and ignoring established authority all contribute to the high levels of stress on nurses. The undisputable significance of emotional intelligence in the sphere of nursing education has led in a rapid increase in the number of emotional intelligence courses and training program that offer a broad range of educational different outcomes to the students. There is a lack of studies regarding to improve teaching and learning in Libyan nursing educational institutions. Quite a few emotional intelligence (EI) assessment studies were found that simply contain criteria and dimensions of EI in the literature study. The aim of this study is to review the emotional intelligence studies in nursing education. This evaluation encompasses a range of publications released throughout the time frame of 2019 to 2023. The findings showed that there is a need for including emotional intelligence program in curriculum of nursing education. In addition, the findings indicated that EI intervention program could boost student academic achievements and alleviate work stress to nurse profession. The discussion chiefly emphasizes on the contemporary issues that are being confronted by the field, as well as the openings for research that exist in the area.